2019
DOI: 10.1016/j.cgh.2018.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Increased Risk of De Novo or Recurrent Hepatocellular Carcinoma in Patients With Cirrhosis Treated With Direct-Acting Antivirals for HCV Infection

Abstract: BACKGROUND & AIMS:Patients with cirrhosis and hepatitis C virus (HCV) infection treated with direct-acting antivirals (DAAs) are still at risk for developing hepatocellular carcinoma (HCC). We aimed to identify features of de novo or recurrent HCCs in these patients, and factors associated with HCC development, in a large cohort of patients with cirrhosis who received treatment with DAAs. METHODS:In a retrospective study, we collected data from 565 patients with cirrhosis (median age, 64 years; range, 28-87 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(114 citation statements)
references
References 23 publications
7
102
0
5
Order By: Relevance
“…Degasperi et al [ 102 ] showed similar results in a retrospective study on 505 cirrhotic patients DAAs treated, demonstrating that a baseline LS > 30 kPa was an independent predictor of de novo HCC, being that the 3-year estimated incidence of de novo HCC was 20% in patients with LSM > 30 kPa versus 5% in patients with LSM ≤ 30 kPa ( p = 0.0003). Recently, in a population of 640 HIV/HCV co-infected patients followed for a median period of 31.6 months post-SVR by DAAs, with the aim of verifying the incidence of HCC, it was shown that none of the 374 patients with LS < 14 kPa at baseline developed HCC [ 103 ].…”
Section: Predictive Factors Of Hcc Appearance or Recurrencementioning
confidence: 65%
See 1 more Smart Citation
“…Degasperi et al [ 102 ] showed similar results in a retrospective study on 505 cirrhotic patients DAAs treated, demonstrating that a baseline LS > 30 kPa was an independent predictor of de novo HCC, being that the 3-year estimated incidence of de novo HCC was 20% in patients with LSM > 30 kPa versus 5% in patients with LSM ≤ 30 kPa ( p = 0.0003). Recently, in a population of 640 HIV/HCV co-infected patients followed for a median period of 31.6 months post-SVR by DAAs, with the aim of verifying the incidence of HCC, it was shown that none of the 374 patients with LS < 14 kPa at baseline developed HCC [ 103 ].…”
Section: Predictive Factors Of Hcc Appearance or Recurrencementioning
confidence: 65%
“…Several studies have shown that the male sex, diabetes and elevated serum alpha-fetoprotein levels before and after DAAs treatment are significant predictors of the onset or recurrence of HCC [ 34 , 39 , 66 , 67 , 102 ].…”
Section: Predictive Factors Of Hcc Appearance or Recurrencementioning
confidence: 99%
“…In a recent study of 565 cirrhotic patients from Italy that were followed for a median period of 25 months, both type 2 DM and high LSM were associated with de novo occurrence of HCC during follow‐up . Nonetheless, baseline LS was not reported in this study and its cohort had an immanent bias because all the patients were cirrhotic at baseline.…”
Section: Discussionmentioning
confidence: 79%
“…Calvaruso et al 31 on the other hand found that low albumin and reduced baseline platelet levels were associated with increased HCC incidence. Lastly Degasperi et al, 32 found male sex and diabetes to be independent predictors of HCC incidence in 565 cirrhotic patients treated with DAAs and followed up for a median time of 25 months after starting antiviral therapy. Host genetic factors may also be involved in HCC development.…”
Section: Hepatic Complications: Hccmentioning
confidence: 99%